Aging, Health Economics, and Tobacco Taxation in Spain: Laffer Curve Insights for Fiscal and Health Policy - Almeida, Alejandro; Golpe, Antonio; Martín-Álvarez, Juan Manuel; Vides, José Carlos; Galiano, Aida (Springer Nature Switzerland, 2025)
Understanding the impact of tobacco taxation is essential for shaping policies that effectively reduce consumption, improve public health, and generate fiscal revenue. This study examines these dimensions by reviewing key research on how tobacco taxes influence smoking behavior, promote cessation, and affect economic equity. We also explore the concept of the Laffer Curve to assess how optimal tax rates can maximize revenue without significantly diminishing demand, drawing lessons from international studies. Focusing on the Spanish context, we analyze recent trends in substitution effects, affordability, and the current performance of tobacco tax policies. Using provincial panel data and econometric techniques, this study aims to provide evidence-based insights into Spain’s tobacco tax structure, offering recommendations for potential reforms to enhance both health and fiscal outcomes.
Keywords: Spain; aging; health economics; tobacco taxation; laffer curve; data-driven